A Vehicle – Bridge Interaction - Jozef Melcer (Communications - Scientific letters of the University of Zilina, 2007)
The problem of a vehicle – bridge interaction can be followed in the literature since the year 1849. At the early state the analytical methods were applied. The development of computers brings the change in the approach to the used methods of solution. The Finite Element Method and Component Element Method represent the revolution and qualitative jump in the development. They enable to solve very truthful space computing models numerically. The results of numerical computation must by verified by the in situ experimental measurements. Mutual interconnection of numerical and experimental techniques represents the most effective way in the process of uncovering of objective reality concerning of real action of bridge structure under the passing of vehicles.